2021
DOI: 10.1111/jcpe.13462
|View full text |Cite
|
Sign up to set email alerts
|

The 2018 EFP/AAP periodontitis case classification demonstrates high agreement with the 2012 CDC/AAP criteria

Abstract: Aim To investigate the agreement between the 2018 EFP/AAP periodontitis case classification and the 2012 CDC/AAP criteria. Materials and Methods This cross‐sectional study assessed a population‐based sample from a rural area in southern Brazil. A complete periodontal examination was performed at six sites/tooth. The periodontitis case definition was estimated and compared according to the 2018 EFP/AAP classification and the 2012 CDC/AAP criteria (reference). Diagnostic tests included sensitivity (SN), specific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
35
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(46 citation statements)
references
References 40 publications
5
35
2
Order By: Relevance
“…The higher frequency of severe cases is in agreement with other studies reporting more severe conditions revealed by the 2018 EFP/AAP classification/case definition system that included mild forms of the former classification in stage II (moderate) of the actual 2018 EFP/AAP classification/case definition system. However, in contrast to our findings, previous results indicated a 100% agreement between classifications for the severe category [43].…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…The higher frequency of severe cases is in agreement with other studies reporting more severe conditions revealed by the 2018 EFP/AAP classification/case definition system that included mild forms of the former classification in stage II (moderate) of the actual 2018 EFP/AAP classification/case definition system. However, in contrast to our findings, previous results indicated a 100% agreement between classifications for the severe category [43].…”
Section: Discussioncontrasting
confidence: 99%
“…A high PPV was calculated by the present study when severe and moderate periodontitis were considered separately. Both PPV and NPV are important parameters for already diagnosed individuals [43]. A moderate periodontitis, diagnosed according to the former classification system, would be referred and treated by dental practitioners; however, according to the 2018 classification system, the same condition would be categorized as severe, and the patient could benefit from a more specialized treatment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is necessary to clarify that, even though the objectives are the same, the methods used in these studies are different. Similar to the present study, Ortigara et al 32 . used only the disease classification stages.…”
Section: Discussionmentioning
confidence: 74%
“…Participants will be divided into two groups: (1) participants without periodontitis and (2) those with a diagnosis of periodontitis (mild, moderate and severe) based on Centers for Disease Control and Prevention and American Academy of Periodontology (CDC/AAP) definition (47), suggested for epidemiological studies by Holtfreter et al (48). According to a recent agreement among experts from Europe and USA (48) and recent epidemiologic trends, the 2012 CDC/AAP criteria become a consensus approach for epidemiological studies worldwide (49). Furthermore, the 2017 World Workshop on the Classification of Periodontal and Peri-Implant Diseases and Conditions (50), in Appendix B, recommended that After a long-standing debate on how to provide data to inform surveillance of periodontal disease, a recent multinational effort has suggested standard reporting of periodontal epidemiology surveys.…”
Section: Periodontitismentioning
confidence: 99%